THE PURE THEORY OF LAW: HANS KELSEN - Situngkir, Danel Aditia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The law of positivism for Hans Kelsen is that it must be cleared of non-juridical elements, such as sociological, political, historical and even ethical elements. This thinking is known as pure legal theory. For him, law is a necessity that regulates human behavior as rational creatures. In Indonesia, law has a very broad scope, not limited to textual provisions in the form of statutory regulations. The functioning of law in society does not only require laws but requires other things such as community culture, law enforcement officers and facilities and infrastructure. From this we can see that positivism tries to confine the law to only textual matters.Keywords: The Pure Theory of Law, Hans Kelsen